2013
DOI: 10.1080/10640266.2013.779188
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Eating and Clinical Symptoms Over the Course of a Day Hospital Program for Eating Disorders

Abstract: Although it is well-established that day hospital programs for eating disorders significantly reduce clinical symptoms, the pre-test/post-test designs that were previously used do not provide information regarding the trajectory of symptoms during treatment. This study observed, on a weekly basis, the evolution of symptoms of 61 women suffering from eating disorders engaged in a day hospital program, and compared the trajectories of specific subgroups of patients. Results show that (a) the first half of the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 28 publications
(36 reference statements)
2
8
0
Order By: Relevance
“…Reductions in EDE‐Q scores were seen for all patients, as well as reductions in the frequency of binge eating and vomiting for those who engaged in these behaviors. Our findings parallel others who have shown DTPs to be effective in reducing ED symptoms . Although rates of binge eating and purging remained moderate at the end of treatment, our reductions are in line with the magnitude of reductions found in other studies .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Reductions in EDE‐Q scores were seen for all patients, as well as reductions in the frequency of binge eating and vomiting for those who engaged in these behaviors. Our findings parallel others who have shown DTPs to be effective in reducing ED symptoms . Although rates of binge eating and purging remained moderate at the end of treatment, our reductions are in line with the magnitude of reductions found in other studies .…”
Section: Discussionsupporting
confidence: 91%
“…2,3,[8][9][10] Furthermore, available longitudinal research has suggested that treatmentrelated changes are maintained at follow-up, with weight gain obtained during day hospital treatment being maintained 6 months after treatment. 4 In treating eating disorders (EDs), day programs offer various clinical and economic advantages over inpatient programs: day treatments promote greater autonomy; they help patients maintain active social, occupational or academic roles 5 ; patients return to their home environment on evenings and weekends, and therefore have more opportunities to integrate changes that they are making during the intensive treatment program 11 ; and financial costs associated with day treatment are substantially lower than those of inpatient treatment. However, the increased time spent away from the supports of treatment in a day hospital program also allows patients more occasions to engage in disordered eating behaviors in their home environments (e.g., restriction, binge-eating, or compensatory behaviors; see Ref.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of patients' engagement with treatment in DTPs, Begin et al (2013) found that the first half of the programme was determinant in relation to symptom-change, and that better respondents to treatment reached the non-clinical cut-off point more rapidly, regardless of baseline levels of eating, depression, anxiety and motivation. This finding reflects earlier evidence that DTP patients who are quick to engage with treatment have better outcomes (Olmsted et al , 1996).…”
Section: Symptom-frequency Change Among Participants With Binge/vomitmentioning
confidence: 97%
“…The importance of early response notwithstanding, past studies have been unable to identify characteristics that differentiate patients who will and will not have a rapid response to treatment (Linardon, Brennan, & de la Piedad Garcia, 2016 To our knowledge, only two studies have examined heterogeneity in treatment response to partial hospitalization for AN (Bégin et al, 2013;Makhzoumi et al, 2017). Bégin's study of 61 adult women examined symptom trajectories of completers, noncompleters, betterrespondents, and poorer-respondents, but did not examine variables predicting different trajectories.…”
Section: Introductionmentioning
confidence: 99%